CONTROLE QUÃMICO DE Aulacaspis tubercularis NEWATEAD, (HEMIPTERA: DIASPIDIDAE) EM POMAR DE MANGA (Mangifera indica L.) - Potenza, Marcos Roberto; Sato, MÃ¡rio Eidi; Raga, Adalton; Souza Filho, Miguel F. de (REVISTA DE AGRICULTURA, 2015)
CONTROLE QUÃMICO DE Aulacaspis tubercularis NEWATEAD, (HEMIPTERA: DIASPIDIDAE) EM POMAR DE MANGA (Mangifera indica L.)